Efektivitas Model Discovery Learning Berbasis Metakognitif dalam Meningkatkan Keterampilan Berpikir Kritis dan Kemampuan Kognitif Siswa pada Materi Fluida Dinamis - Alya Alimatul Zahro; Parlindungan Sinaga; Agus Danawan (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
This research aims to investigate the effectiveness of metacognition-based discovery learning models in improving students' critical thinking skills and cognitive abilities as well as the relationship between the two variables on dynamic fluid materials. This research uses a quasi-experimental quantitative method with a nonequivalent control group design. The population of this research is all grade XI students in one of the State High Schools in Bandung City. The sample of this research was obtained using the convenience sampling technique, obtained from class XI-2 as the experimental class and class XI-4 as the control class. The instrument used to measure cognitive ability is multiple-choice test questions with 13 questions, while to measure critical thinking skills, multiple-choice test questions with 7 questions are used. The data analysis technique uses N-Gain, effect size, linear regression, and correlation analysis. The results of the research showed that there was a difference in improving cognitive ability and critical thinking skills. For the experimental class, N-Gain was obtained of 0.70 and 0.68, respectively, which was a greater increase compared to the control class, namely with N-Gain values of 0.44 and 0.36, respectively. The metacognition-based discovery learning model has an impact on improving students' cognitive abilities and critical thinking skills with effect size values of 1.83 and 1.85 respectively with high categories. Cognitive ability is quite influential in improving critical thinking skills with a correlation coefficient of 0.40.